From HEP to medical radiation dosimetry - The silicon strip detector dose magnifying glass - Wong, J.H.D.; Cutajar, D.; Lerch, M.L.F.; Petasecca, M.; Knittel, T.; Carolan, M.; Perevertaylo, V.L.; Metcalfe, P.; Rosenfeld, A.B. (Elsevier, 2011)
High energy physics (HEP) experiments and research gave rise to the development of high spatial resolution tracking vertex detectors and the accompanying data acquisition systems (DAQ) capable of high temporal resolution measurements. The technology translation from HEP to the day to day medical radiation dosimetry is gradual but certain. This paper discusses the design and development of a high spatial resolution (0.2 mm pitch) silicon strip detector referred to as the Dose Magnifying Glass designed and prototyped by the Centre for Medical Radiation Physics (CMRP), University of Wollongong. The DMG has 128 phosphor implanted n(+) strips on a p-type silicon wafer coupled to a TERA readout system. The preirradiated low resistivity device was found to be dose rate independent (1.1%) for the dose rate of 9.45 x 10(-5) to 2.72 x 10(-4) Gy/pulse. The effect of detector packaging was studied. The application of DMG in small field dosimetry was demonstrated in the real time measurement of stereotactic radiosurgery cone profiles and the imaging of I-125 brachytherapy seeds. The DMG, a concept once started in the HEP experiments, now offers new possibilities in medical radiation dosimetry. (C) 2011 Elsevier Ltd. All rights reserved.